Optimalisasi Potensi Pada Bank Sampah Pelita Borneo Balikpapan - Cipto, Rahajeng Cahyaning Putri; Go Novia Amelinda Gotama; Rina Permata Sari Sumitro; Adinda Zulhidayatul Zariah; Boby Dwi Ardhana (Komunal Jurnal Pengabdian Masyarakat, 2023)
This activity is carried out by UMKM. After we have carried out a survey of UMKM in Baru Tengah Subdistrict and determined the targets for UMKMs that we will provide assistance to, namely the Waste Bank Business which is located at RT.38 Jl. Student Hill No.27 Baru Tengah Village, West Balikpapan District. The problem faced by these business actors is that they do not have digital-based marketing and require the development of more varied innovations and do not have simple financial records. The results of this activity are in the form of innovative development of products developed by the Waste Bank and the creation of social media to expand cooperation networks to all parties.